Defect chemistry and defect engineering of TiO2-based semiconductors for solar energy conversion. (8th October 2015) - Nowotny, Janusz; Alim, Mohammad Abdul; Bak, Tadeusz; Idris, Mohammad Asri; Ionescu, Mihail; Prince, Kathryn; Sahdan, Mohd Zainizan; Sopian, Kamaruzzaman; Mat Teridi, Mohd Asri; Sigmund, Wolfgang
Abstract : This review considers defect chemistry of TiO2 and defect-related properties associated with solar energy conversion. Abstract : This tutorial review considers defect chemistry of TiO2 and its solid solutions as well as defect-related properties associated with solar-to-chemical energy conversion, such as Fermi level, bandgap, charge transport and surface active sites. Defect disorder is discussed in terms of defect reactions and the related charge compensation. Defect equilibria are used in derivation of defect diagrams showing the effect of oxygen activity and temperature on the concentration of both ionic and electronic defects. These defect diagrams may be used for imposition of desired semiconducting properties that are needed to maximize the performance of TiO2 -based photoelectrodes for the generation of solar hydrogen fuel using photo electrochemical cells (PECs) and photocatalysts for water purification. The performance of the TiO2 -based semiconductors is considered in terms of the key performance-related properties (KPPs) that are defect related. It is shown that defect engineering may be applied for optimization of the KPPs in order to achieve optimum performance.